Acquired Ptosis in Patient with Suspect Meningiomatosis - Moch. Fahmi; Nella Lusti Widhianingsih (Magna Neurologica, 2024)
Background: Ptosis is abnormally low positioned upper eyelid. It can be classified as congenital and acquired. Meningiomas are mostly benign tumors originating from meningothelial (arachnoid) cells (MECs). A subset of meningioma patients bears two or more spatially separated synchronous or metachronous tumors termed “Multiple Meningiomas” (MM) or meningiomatosis. Case: A 51-year-old female complained the dizziness was associated with nausea and emetic episodes. She reported any blurred vision and woke up with the dropped eyelid. Prior to this she had double vision and light headedness that she had 3 months before. The ophthalmic examination presented partial left ptosis and the patient's left eye was shifted towards the lateral edge at rest. CT scan with contrast presented multiple solid masses, extra axial, homogeneous, strong contrast enhancement with calvaria hyperostosis and perifocal edema in the left frontal region and left temporoparietal region. Discussion: Ptosis in the left eye and exotropia is consistent with a left oculomotor nerve palsy. CT scan with contrast confirmed multiple solid masses leaning towards meningiomatosis. In this case, patient-acquired ptosis could be caused by direct oculomotor compression of the frontal lobe tumor, the tumor site being close to the superior orbital fissure. Conclusion: Stemming from third cranial nerve dysfunction, multiple solid masses in the left frontal region indicate meningiomatosis. Acquired ptosis may result from direct compression of the oculomotor nerve by the frontal lobe tumor. While surgery is the primary treatment for meningiomas, corticosteroids may be considered in acute conditions to alleviate perifocal edema.